Comparative Drug Release Investigations for Diclofenac Sodium Drug (DS) by Chitosan-Based Grafted and Crosslinked Copolymers - Chopra L.; Thakur K.K.; Chohan J.S.; Sharma S.; Ilyas R.A.; Asyraf M.R.M.; Zakaria S.Z.S. (MDPI, 2023)
Acrylic monomers; Ascorbic acid; Chitosan; Controlled drug delivery; Graft copolymers; Grafting (chemical); Hydrogels; Scanning electron microscopy; Sodium; Targeted drug delivery; Acrylamides; Crosslinked; Diclofenac sodium; Drug release; Equilibration process; Ficks law; Graft- copolymers; PH-responsive; Sodium diclofenac; Sustainable drug release; Amides